A comparable study of Fe//MCs (M = Ti, V) interfaces by first-principles method: The chemical bonding, work of adhesion and electronic structures. (March 2020) - Chen, Lu; Li, Yefei; Peng, Jianhong; Sun, Liang; Li, Bo; Wang, Zhicheng; Zhao, Siyong
Abstract: The work of adhesion ( W ad ), interfacial fracture toughness ( K I c int ), and electronic structure of the Fe(100)//MCs(100) (M = Ti and V) interfaces have been investigated by means of first-principles calculations. Considering two types of interfaces (type 1 and 2), two MCs (TiC and VC) and three different atomic stacking sequences (Fe-on-M, Fe-on-C and Bridge), totally twelve candidate interfacial configurations were analyzed. It is found that the W ad decreases with the order of Fe-on-C > Bridge > Fe-on-M. With the larger W ad, the type 2 Fe//MCs interfaces are more stable than type 1 Fe//MCs interfaces, in which the Fe-on-C site for type 2 Fe//VC interfaces belongs to the most stable interfacial configuration. Based on the Griffith's theory, the mechanical failure of both type 1 and type 2 Fe//TiC interfaces are more inclined to initiate at the interface. While for the Fe-on-C and Bridge site of both type 1 and type 2 Fe//VC interfaces, the mechanical failure will occur at the VC bulk phases rather than at the interface. Besides, the interfacial fracture toughness of Fe-on-C site for the type 2 Fe//VC structure is the best. The interfacial bonding character of Fe-on-C site for both Fe//TiC and Fe//VC interfaces have been investigated based on the electronic density of states and charge density difference. A mixed covalent/ionic/metallic bonding is revealed between iron and transition metal carbides. Further analysis of mulliken population and magnetic moment of interfacial atoms indicates that the Fe//VC interfaces show higher bonding strength than Fe//TiC interfaces. Graphical abstract: The high electronic density between interfacial Fe and C atoms indicates the formation of the strong interfacial covalent Fe–C bonds, where Fe//VC interfaces exhibit stronger interfacial bonding than Fe//TiC interfaces. Image 1 Highlights: Fe//MCs interfaces were studied to reveal their adhesion strength, fracture mechanism and interfacial bonding. The interfacial bonding strength of the Fe-on-C site for the type 2 Fe//VC interface is the highest. The mechanical failure of Fe//TiC interfaces is inclined to initiate at the interface rather than the bulk sides. Fe//VC interfaces are predicted to fail at the VC bulk side rather than at the interface.